2020
DOI: 10.3390/cells9030695
|View full text |Cite
|
Sign up to set email alerts
|

ER Stress Responses: An Emerging Modulator for Innate Immunity

Abstract: The endoplasmic reticulum (ER) is a critical organelle, storing the majority of calcium and governing protein translation. Thus, it is crucial to keep the homeostasis in all ER components and machineries. The ER stress sensor pathways, including IRE1/sXBP1, PERK/EIf2α and ATF6, orchestrate the major regulatory circuits to ensure ER homeostasis. The embryonic or postnatal lethality that occurs upon genetic depletion of these sensors reveals the essential role of the ER stress pathway in cell biology. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(130 citation statements)
references
References 70 publications
1
109
0
Order By: Relevance
“…Prolonged UPR has been shown to be proinflammatory [32,33].Therefore, we next sought to determine if leukocyte adhesion to AngII exposed VSMCs could be mitigated by the ER chaperone treatment. THP-1 monocyte recruitment assay with VSMCs was utilized to simulate vascular inflammation [34].…”
Section: Angii-induced Proinflammatory Phenotype Is Mitigated By Grp78mentioning
confidence: 99%
“…Prolonged UPR has been shown to be proinflammatory [32,33].Therefore, we next sought to determine if leukocyte adhesion to AngII exposed VSMCs could be mitigated by the ER chaperone treatment. THP-1 monocyte recruitment assay with VSMCs was utilized to simulate vascular inflammation [34].…”
Section: Angii-induced Proinflammatory Phenotype Is Mitigated By Grp78mentioning
confidence: 99%
“…Accumulating studies have shown that cellular ERS promotes the expression of pro-inflammatory cytokines (such as IFN-γ and TNF-α) and then participates in the regulation of innate and adaptive immunity [33,34]. Both IFN-γ and TNF-α belong to the Th1-type cytokines and play significant roles in the regulation of cellular immune responses to intracellular microbial infections [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence have revealed that many stressorsinduced cellular ERS can promote the expression of inflammatory cytokines and then participate in the regulation of innate immunity [33,34]. Many proinflammatory cytokines, such as interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α), can promote induction of autophagy [35,36].…”
Section: The Perk and Ire1 Pathways Are Associated With Transcriptionmentioning
confidence: 99%
“…Macrophage activation occurs through the DAMP (damage-associated molecular patterns) and PAMP (pathogen-associated molecular patterns) interaction with TLR [ 95 ]. TLR activation leads to the IRE1α/XBP1 signaling pathway (UPR activation) induction and subsequent production of the pro-inflammatory cytokines IL6, CCL2, and TNF-α.…”
Section: Relationship Between Cholesterol Accumulation Er Stressmentioning
confidence: 99%